2017
DOI: 10.1186/s12942-017-0104-x
|View full text |Cite
|
Sign up to set email alerts
|

Relative risk estimation of dengue disease at small spatial scale

Abstract: BackgroundDengue is a high incidence arboviral disease in tropical countries around the world. Colombia is an endemic country due to the favourable environmental conditions for vector survival and spread. Dengue surveillance in Colombia is based in passive notification of cases, supporting monitoring, prediction, risk factor identification and intervention measures. Even though the surveillance network works adequately, disease mapping techniques currently developed and employed for many health problems are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Nine studies used geographic characteristics in their model. Altitude [ 26 28 ] and mean vegetation index [ 29 , 46 , 47 ] were the most common features used. Out of nine geographic variables applied, most studies used only one indicator.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies used geographic characteristics in their model. Altitude [ 26 28 ] and mean vegetation index [ 29 , 46 , 47 ] were the most common features used. Out of nine geographic variables applied, most studies used only one indicator.…”
Section: Resultsmentioning
confidence: 99%
“…Martínez-Bello et al . [ 46 ] compared CAR BYM (Besag, York and Mollié) [ 62 ] prior and Leroux CAR prior [ 63 ] for spatially structured random effects for estimating relative risk of dengue. They found that the CAR BYM prior was better than the Leroux CAR prior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative risk estimation of dengue disease has been developed using spatial and spatio-temporal data at several spatial resolutions. For example, spatial modeling of dengue data has been applied to data from Brazil [ 12 ] and Colombia [ 13 ], while spatio-temporal dengue data have been analyzed using relative risk models in Brazil [ 14 16 ], Ecuador [ 17 ], Thailand [ 18 ], Colombia [ 19 ] [ 20 ], and Indonesia [ 21 ]. However, most of these analyses did not fully explore the space-time interaction effect model framework.…”
Section: Introductionmentioning
confidence: 99%
“…Racloz et al ( 6 ) and Louis et al ( 7 ) reviewed the spatial patterns assessment of dengue risk; specifically for RR estimation of dengue, Ferreira and Schmidt ( 8 ) and Martínez-Bello et al ( 9 ) estimated RR for dengue on a local spatial scale; and Restrepo et al ( 10 ) and Martínez-Bello et al ( 11 ) applied methods for the spatiotemporal assessment of dengue risk. Examples for the spatial patterns assessment of Zika risk run from merely descriptive methods to model-based approaches.…”
mentioning
confidence: 99%